Association Between Obsessive-Compulsive Symptom Dimensions in Mothers and Psychopathology in Their Children - Blanco-Vieira, Thiago; Hoexter, Marcelo Queiroz; Batistuzzo, Marcelo C.; Alvarenga, Pedro; Szejko, Natalia; Fumo, Afonso Mazine Tiago; Miguel, Eurípedes C.; do Rosário, Maria Conceição (Frontiers in Psychiatry, 2021)
Background: The non-clinical presentation of obsessive–compulsive symptoms (OCS) in women may impact not only their daily lives and wellbeing but also increase the risk for emotional and behavioral problems in their children. This study aims to investigate the OCS dimension distribution in a large sample of mothers from a cohort of school age children and the association between these OCS dimensions with their own psychopathology, and with the presence of OCS and other psychopathology in their children. Method: Our final sample consisted of 2511 mother-children dyads recruited from the elementary schools of two large cities. Throughout multiple regression analysis, we examined the correlations between demographic and clinical variables of mothers assessed by the Mini International Psychiatric Interview (MINI) and the Dimensional Yale-Brown Obsessive-Compulsive Scale-Brief Version (DY-BOCS-Brief) with children’s psychopathology status reported by the Child Behavior Checklist (CBCL). Results: The overall prevalence of mothers who reported experiencing at least one OCS was 40% (N=1,004). “Aggression/violence” was the most frequent symptom dimension (32.2%), followed by the “symmetry/ordering” (16.4%) and the “sexual/religious” dimensions (13.8%). There was a significant correlation between the presence of OCS and maternal psychopathology in general (p<.001, r=.397). Not only the presence but also the severity of the mother’s OCS were strongly correlated to the total (p-value <.001), internalizing (p-value<.001), externalizing (p-value.001) and OCS subscale scores (p-value< .001) on the CBCL. Conclusion: OCS dimensions are highly prevalent in women. Presence and severity of maternal OCS are related to children´s psychopathology and behavioral problems.